Evapotranspiração, crescimento e produção da melancia e melão irrigados com águas de diferentes salinidades: Vladimir Batista Figueirêdo. - - Figueirêdo, Vladimir Batista [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
planejamento mais eficaz do aproveitamento da água na agricultura, e o desenvolvimento de tecnologias que permitam estimar volumes cada vez mais exatos para a melhor eficiência da irrigação, têm papel fundamental para se alcançar ótimas produções agrícolas, aliada a melhor qualidade. Nesse caso a exata determinação da evapotranspiração da cultura (ETc) é um ponto crucial para o uso eficiente da água, bem como pelo fato da atual escassez dos recursos hídricos, principalmente em regiões áridas e semi-áridas, fazendo com que se utilize da água salina para irrigação. Diante disso, o presente trabalho teve como objetivo determinar a evapotranspiração da melancia e melão, em diferentes níveis de salinidade da água de irrigação e verificar seus efeitos no crescimento e na produção destas culturas. Para tanto foram realizados dois experimentos em campo, na Fazenda Experimental da Alagoinha pertencente a Universidade Federal Rural do SemiÁrido situada em Mossoró-RN, com melancia e posteriormente com melão, na mesma área, medindo 0,24 ha. Os níveis de salinidade da água de irrigação foram de S1=0,55, S2=1,65, S3=2,35, S4=3,5 e S5=4,5 dS m-1 para a melancia e S1=0,57, S2=1,65, S3=2,65, S4=3,45 e S5=4,5 dS m-1 para o melão. Os experimentos constaram de quatro blocos ao acaso com quatro repetições, cada um dividido nos cinco níveis de salinidade e no caso do melão em mais três níveis de nitrogênio subdivididas em cada parcela de salinidade. Os níveis de nitrogênio aplicados no melão foram de 67,5%, 90% e...

The water agricultural used effective design and the developments of technologies to estimated irrigation water exact are important irrigation management. Once evapotranspiration culture determinations (ETc) is crucial for use efficient irrigation water and irrigation water salinity. The objectives this work were determined evapotranspiration of watermelon and melon, in different levels of irrigation water salinity and verify effects in growth and production of these cultures. Were conducted two experiments in field, watermelon and melon, in same area with 0,24 ha. The levels of irrigation water salinity were of S1=0.55, S2=1.65, S3=2.35, S4=3.5 and S5=4.5 dS m-1 for watermelon and S1=0.57, S2=1.65, S3=2.65, S4=3.45 and S5=4.5 dS m-1 for melon. The experiments was four randomized blocks with four replications, divided in five salinity levels and in the case of melon in more three levels of nitrogen subdivided. The levels of nitrogen applied were of 67.5%, 90% and 135% of the applied dose (92.5 kg ha-1). The determination of evapotranspiration reference (ETo) was realized by method Penmam-Monteith-FAO through from formulations by Allen et al. (2006), and the ETc readings from two weight lysimeters installed in S1 and S5. The results showed that ETc of watermelon decreases between S1 and S5 where the total evapotranspiration was 245 and 214 mm, respectively. In melon the ETc also decreased between the two salinities, but was observed reduction 0.56 for S1, and 0.22, 0.64, 0.98 and 0.40values for the S5 in the watermelon. In melon observed medium Kc of 0.14, 0.57, 1.13, 0.66 for S1, and 0.11, 0.34, 0.91 0.54 for the S5 respectively. These values of Kc are verified for S1 was larger than Kc recommended by FAO (Allen et al., 2006), excepting for stage initial and final of each culture, and smaller for the S5, so much for melon as watermelon. There wasn’t significant ...(Complete abstract click electronic access below)
Keywords: Melão; Melancia; Agua - Salinidade; Evapotranspiração; Water salinity; Melon; Evapotranspiration; Watermelon